Performance Analysis of Increased Safety HT Induction Motor with Higher Stator Coil Pitch for Classified Hazardous Area - B. Ahirwal; T. K. Chatterjee (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2014)
The increased safety (Ex e) high tension (HT) motors are widely used in the petroleum industries and area where explosive atmosphere is present. The time tE and IA/IN ratio value is very important for Ex e motor. The time tE of rotor and or stator winding, IA/IN ratio and temperature rise can be affected by increasing the stator coil pitch. The coil pitch of stator were increased for three different ratings of three phase HT Ex e induction motors and redesigned for analyzing the temperature rise, tE and performance. The relevant tests were performed and performance characteristic of motor was compared with normal design motor. The Ex e motors mentioned in this paper had been manufactured by Bharat Heavy Electricals Ltd. (BHEL), Bhopal, India during the project as per the design and guidance of main author as project leader. It is anticipated that the research work presented in this paper will be of immense benefit to Ex e HT motor designers.